Seasonal Variability in Near-bed Environmental Conditions in the Vazella pourtalesii Glass Sponge Grounds of the Scotian Shelf - Hanz, Ulrike; Beazley, Lindsay; Kenchington, Ellen; Duineveld, Gerard; Rapp, Hans Tore; Mienis, Furu (Frontiers in Marine Science, 2021)
The Scotian Shelf harbors unique aggregations of the glass sponge Vazella pourtalesii that provides an important habitat for benthic and pelagic fauna. Recent studies have shown that these sponge grounds have persisted in the face of strong inter-annual and multi-decadal variability in temperature and salinity. However, little is known of these environmental characteristics on hourly-seasonal time scales. This study presents the first hydrodynamic observations and associated (food) particle supply mechanisms for the Vazella sponge grounds, highlighting the influence of natural variability in environmental conditions on sponge growth and resilience. Near-bottom environmental conditions were characterized by high temporal resolution data collected with a benthic lander, deployed during a period of 10 months in the Sambro Bank Sponge Conservation Area. The lander was equipped with temperature and oxygen sensors, a current meter, a sediment trap and a video camera. In addition, water column profiles of temperature and salinity were collected in an array across the sponge grounds from high to lower sponge presence probability. Over the course of the lander deployment, temperature fluctuated between 8.8 - 12 °C with an average of 10.6 ± 0.4 °C. Dissolved oxygen concentration was on average 6.3 mg l-1, and near-bottom current speed was on average 0.12 m s-1, with peaks up to 0.47 m s-1. Semi-diurnal tidal currents promoted constant resuspension of particulate matter in the benthic boundary layer. Surface storm events episodically caused extremely turbid conditions on the seafloor that persisted for several days, with particles being resuspended to more than 13 m above the seabed. The carbon flux in the near-bottom sediment trap peaked during storm events and also after a spring bloom in April, when fresh phytodetritus was observed in the bottom boundary layer. While resuspension events can represent a major stressor for sponges, limiting their filtration capability and remobilizing them, episodes of strong currents and lateral particle transport likely play an important role in food supply and the replenishment of nutrients and oxygen. Our results contextualize human-induced threats such as bottom fishing and climate change by providing more knowledge of the natural environmental conditions under which sponge grounds persist.